Neutron diffraction from aligned stacks of lipid bilayers using the WAND instrument. Issue 2 (21st February 2018) - Marquardt, Drew; Frontzek, Matthias D.; Zhao, Yu; Chakoumakos, Bryan C.; Katsaras, John
Abstract : The implementation is described of neutron diffraction from aligned lipid bilayer stacks on the Wide‐Angle Neutron Diffractometer (WAND), located at the High Flux Isotope Reactor, Oak Ridge, Tennessee, USA. Abstract : Neutron diffraction from aligned stacks of lipid bilayers is examined using the Wide‐Angle Neutron Diffractometer (WAND), located at the High Flux Isotope Reactor, Oak Ridge, Tennessee, USA. Data were collected at different levels of hydration and neutron contrast by varying the relative humidity (RH) and H2 O/D2 O ratio from multi‐bilayers of dioleoylphosphatidylcholine and sunflower phosphatidylcholine extract aligned on single‐crystal silicon substrates. This work highlights the capabilites of a newly fabricated sample hydration cell, which allows the lipid bilayers to be hydrated with varying H/D ratios from the RH generated by saturated salt solutions, and also demonstrates WAND's capability as an instrument suitable for the study of aligned lipid multi‐bilayers.